Kiss me deadly: From Finnish great depression to great recession - Adam Gulan; Markus Haavio; Juha Kilponen (Bank of Finland, 2014)
We investigate the causes of the Finnish Great Depression, 1990-1993. We find that the collapse of the overheated financial and banking sectors starting in 1989 was the trigger of the economic crisis. Foreign shocks, which include the collapse of trade with USSR in 1991, can account for at most about half of the slump, and these shocks occurred only when the economy was already in free fall. Also, the deleveraging and restructuring process of the financial system substantially prolonged the subsequent recovery. Our methodology involves estimating a structural VAR model with sign and exogeneity restrictions. Importantly, we are able to distinguish between financial shocks affecting the demand for intermediated loans and those shifting the loan supply curve. Hence we also contribute to the discussion on which financial shocks actually matter.
URN:NBN:fi:bof-201411193261
Keywords: E32; E44; O52; 330; business cycles; great depressions; financial shocks; sign restrictions; Finland